Toll‐like receptor‐2 exacerbates murine acute viral hepatitis. Issue 2 (10th August 2016) - Bleau, Christian; Burnette, Mélanie; Filliol, Aveline; Piquet‐Pellorce, Claire; Samson, Michel; Lamontagne, Lucie
Summary: Viral replication in the liver is generally detected by cellular endosomal Toll‐like receptors (TLRs) and cytosolic helicase sensors that trigger antiviral inflammatory responses. Recent evidence suggests that surface TLR2 may also contribute to viral detection through recognition of viral coat proteins but its role in the outcome of acute viral infection remains elusive. In this study, we examined in vivo the role of TLR2 in acute infections induced by the highly hepatotrophic mouse hepatitis virus (MHV) type 3 and weakly hepatotrophic MHV‐A59 serotype. To address this, C57BL/6 (wild‐type; WT) and TLR2 knockout (KO) groups of mice were intraperitoneally infected with MHV3 or MHV‐A59. MHV3 infection provoked a fulminant hepatitis in WT mice, characterized by early mortality and high alanine and aspartate transaminase levels, histopathological lesions and viral replication whereas infection of TLR2 KO mice was markedly less severe. MHV‐A59 provoked a comparable mild and subclinical hepatitis in WT and TLR2 KO mice. MHV3‐induced fulminant hepatitis in WT mice correlated with higher hepatic expression of interferon‐ β, interleukin‐6, tumour necrosis factor‐ α, CXCL1, CCL2, CXCL10 and alarmin (interleukin‐33) than in MHV‐A59‐infected WT mice and in MHV3‐infected TLR2 KO mice. Intrahepatic recruited neutrophils, natural killer cells, natural killer T cells or macrophages rapidly decreased in MHV3‐infected WT mice whereas they were sustained in MHV‐A59‐infected WT mice and MHV3‐infected TLR2 KO. MHV3 in vitro infection of macrophagic cells induced rapid and higher viral replication and/or interleukin‐6 induction in comparison to MHV‐A59, and depended on viral activation of TLR2 and p38 mitogen‐activated protein kinase. Taken together, these results support a new aggravating inflammatory role for TLR2 in MHV3‐induced acute fulminant hepatitis. Abstract : Recent evidences suggest that surface Toll‐like receptor 2 (TLR2) may also contribute to viral detection through recognition of viral coat proteins but its role in the outcome of acute viral infection remains elusive. Murine hepatitis virus (MHV) 3‐induced fulminant hepatitis in mice correlated with higher hepatic expression of inflammatory cytokines and chemokines, and alarmin interleukin‐33 than in infected TLR2 knockout mice. These results support a new aggravating inflammatory role for TLR2 in viral‐induced acute fulminant hepatitis.